Beyond cure. Issue 5 (September 2015) - Berenguer, Marina; García-Eliz, María; Baiguera, Chiara; Puoti, Massimo
<x xml:space="preserve">Abstract</x> Purpose of review The aim of this review was to define the implication of hepatitis C virus (HCV) eradication in patients with cirrhosis. Recent findings Sustained virologic response (SVR) is associated with a favourable outcome in patients with cirrhosis especially in the presence of regression of cirrhosis but also with extrahepatic outcomes regarding health-related quality of life, risk of diabetes, risk of cardiovascular diseases and control of HIV replication by antiretroviral therapy. In patients with decompensated cirrhosis identifying the point of no return where viral eradication is not followed by clinical improvement is extremely relevant. A strict follow-up is needed in order to early diagnose HCC and signs of liver dysfunction, even after SVR, not only in patients with histological diagnosis of cirrhosis but also in those with advanced disease identified by liver stiffness measurements or by noninvasive methods. Summary Eradication of HCV is associated with regression or 'freezing' of cirrhosis even if it is still unknown the point of no return where this has no benefit for the patient. Nevertheless, in patients with cirrhosis, follow-up should be pursued after eradication of HCV. In addition, HCV eradication has several extrahepatic benefits.